Margaret Atwood’s “Oryx and Crake” as a Critique of Technological Utopianism - KABAK, MURAT (My University, 2021)
While there are major works tracing the themes of belonging and longing for home in contemporary fiction, there is no current study adequately addressing the connection between dystopian novel and nostalgia. This paper aims to illustrate how the Canadian writer Margaret Atwood uses nostalgia as a framework to level a critique against technological utopianism in her dystopian novel Oryx and Crake (2003). The first novel in Atwood’s “MaddAddam Trilogy” problematizes utopian thought by focusing on the tension between two utopian projects: the elimination of all suffering and the perfection of human beings by discarding their weaknesses. Despite the claims of scientific objectivity and environmentalism, the novel exposes the religious and human-centered origins of Crake’s technological utopian project. Atwood’s Oryx and Crake is an ambiguous work of science fiction that combines utopian and dystopian elements into its narrative to criticize utopian thought.
Keywords: Dystopian fiction; Margaret Atwood; Nostalgia; Oryx and Crake; Technological utopianism; Distopik kurgu; Nostalji; Teknolojik ütopyacılık; Oryx ve Crake